ANALISIS TINAJUAN HUKUM TERHADAP PENUNDAAN PELAKSANAAN PEMBAGIAN HARTA WARISAN PADA MASYARAKAT DESA SAWAH KEC KAMPAR UTARA KAB KAMPAR - Putra, Deri Eka (Yurisprudentia: Jurnal Hukum Ekonomi, 2023)
The purpose of this study, entitled "The tradition of implementing inheritance in the Muslim community of Sawah Kec Kampar Utara Kab Kampar according to Islamic law review," is to gain a better understanding of the practice of Islamic law in the distribution of inheritance property in the Muslim community of Sawah Kec Kampar Utara Village. This field research was conducted in Sawah Village, North Kampar District. Primary data from heirs who postpone the division of inheritance and secondary data from relevant public figures, books and articles. The study found that Islamic law requires immediate distribution of the estate left behind after the management of the remains, debts receivable, and will of the deceased is completed.